2021
DOI: 10.1037/trm0000318
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychosocial resources as predictors of posttraumatic growth: A longitudinal study of low-income, female Hurricane Katrina survivors.

Abstract: This study examined how well the Posttraumatic Growth Inventory (PTGI; Tedeschi & Calhoun, 1996) corresponds with self-reported pre-to posttrauma changes in related constructs, including sense of purpose in life, religiosity, and social support. Participants were 328 low-income mothers (85.2% non-Hispanic Black) who survived Hurricane Katrina and completed surveys approximately 1 year predisaster (Time 1), 4 years postdisaster (Time 2), and 12 years postdisaster (Time 3). PTG was assessed at Time 2 and Time 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Consistent with previous research, membership in PTG courses was also related to participants’ sense of purpose in life. Previous research has linked survivors’ sense of purpose in life 4 and 12 years following Hurricane Katrina being associated with higher levels of PTG in survivors of weather-related disasters at those time points (Lowe et al, 2013; Manove et al, 2021). This connection may be driven by items across the PTGI subscales that align with the sense of purpose in life measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous research, membership in PTG courses was also related to participants’ sense of purpose in life. Previous research has linked survivors’ sense of purpose in life 4 and 12 years following Hurricane Katrina being associated with higher levels of PTG in survivors of weather-related disasters at those time points (Lowe et al, 2013; Manove et al, 2021). This connection may be driven by items across the PTGI subscales that align with the sense of purpose in life measured in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PTG at each assessment period was quite low, with means ranging from 36.42 (SD = 1.52) to 39.55 (SD = 1.32) between 18 and 36 months after the fires. Other studies have found higher means among survivors of cancer up to 2 years (M = 51.48) and up to five and a half years after their diagnosis (M = 60.21; Romeo et al, 2020;Weiss, 2002), among bereaved parents up to 8 years (M = 79.72 for fathers and M = 83.47 for mothers) and up to approximately 9 years after their loss (M = 56.80; Polatinsky & Esprey, 2000;, and among tornado and hurricane victims up to 9 months (M = 54.01) and 12 years (M = 59.18) after the disasters (An et al, 2018;Manove et al, 2021). This might suggest that the context surrounding the trauma could have an impact on the PTG level.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic Growth (PTG). The dependent variable for this study was PTG, measured by the Posttraumatic Growth Inventory Short-Form (PTGI-SF) [53] a validated (54,55) and widely used (30,56,57) measure assessing growth because of a stressful or traumatic event derived from the Tedeschi and Calhoun's original Posttraumatic Growth Inventory (PTGI) [58]. The PTGI-SF has been used with healthcare workers during the COVID-19 pandemic [34,59,60] and consists of ten items each with a 0-5 response scale.…”
Section: Materials and Measuresmentioning
confidence: 99%